DEVELOPMENT OF MODERATION OF MODERATE ISLAMIC EDUCATION VALUES THROUGH THE FIVE AWARENESS OF STUDENTS - Munawaroh, Rofi'atul (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
This study aims to analyze and describe moderate Islamic values in the Development of Moderation of Moderate Islamic Education Values through the Five Awareness of Santri Pondok Pesantren Nurul Jadid Paiton Probolinggo. This article describes medium Islamic education through the five awareness of the students. The first Moderate Islamic value that was developed was al-tawazun as an effort so that students have a multicultural mindset and behave in moderation as students and as citizens in general. The Islamic principle of al-tawazun is expected to become a character inherent in students, as well as having complete awareness in the realm of religious understanding, knowledgeable awareness, organizational awareness, community awareness and national and state awareness.